Preparedness for Serious Illnesses: Impact of Ethnicity, Mistrust, Perceived Discrimination, and Health Communication. (April 2022) - Bazargan, Mohsen; Cobb, Sharon; Assari, Shervin; Bazargan-Hejazi, Shahrzad
Background: Increasing severity of serious illness requires individuals to prepare and make decisions to mitigate adverse consequences of their illness. In a racial and ethnically diverse sample, the current study examined preparedness for serious illness among adults in California. Methods: This cross-sectional study used data from the Survey of California Adults on Serious Illness and End-of-Life 2019. Participants included 542 non-Hispanic White (52%), non-Hispanic Black (28%), and Hispanic (20%) adults who reported at least one chronic medical condition that they perceived to be a serious illness. Race/ethnicity, socio-demographic factors, health status, discrimination, mistrust, and communication with provider were measured. To perform data analysis, we used logistic regression models. Results: Our findings revealed that 19%, 24%, and 34% of non-Hispanic White, non-Hispanic Blacks, and Hispanic believed they were not prepared if their medical condition gets worse, respectively. Over 60% indicated that their healthcare providers never engaged them in discussions of their feelings of fear, stress, or sadness related to their illnesses. Results of bivariate analyses showed that race/ethnicity was associated with serious illness preparedness. However, multivariate analysis uncovered that serious illness preparedness was only lower in the presence of medical mistrust in healthcare providers, perceived discrimination, less communication with providers, and poorer quality of self-rated health. Conclusion: This study draws attention to the need for healthcare systems and primary care providers to engage in effective discussions and education regarding serious illness preparedness with their patients, which can be beneficial for both individuals and family members and increase quality of care.